Navigating the Moral Maze: Ethical Challenges and Opportunities of Generative Chatbots in Global Higher Education - Dwi Mariyono; Akmal Nur Alif Hidayatullah (Applied Computational Intelligence and Soft Computing)
The rise of generative artificial intelligence (AI), such as ChatGPT, enhances higher education through personalized learning, administrative automation, and increased accessibility. However, it also raises ethical concerns about data security, academic integrity, algorithmic bias, and learner autonomy. This study employs a Hybrid Thematic SWOT (HT-SWOT) analysis to examine the strengths, weaknesses, opportunities, and threats of generative AI in global higher education. Through a systematic literature review of recent studies (2020–2024), this research highlights both the benefits, such as personalized learning, accessibility, and administrative efficiency, and the risks, including digital divides, misinformation, technosolotionism, and ethical concerns. The findings emphasize the need for responsible AI policies, faculty training, and equitable implementation strategies. This study provides actionable insights for policymakers, educators, and technologists to navigate AI’s ethical integration while promoting global equity and sustainable educational practices. Addressing these challenges requires a balanced approach that safeguards academic integrity while harnessing AI’s potential to enhance education worldwide.